2011
DOI: 10.1002/hbm.21322
|View full text |Cite
|
Sign up to set email alerts
|

Oscillatory correlates of controlled speed‐accuracy tradeoff in a response‐conflict task

Abstract: In making decisions, people have to balance between the competing demands of speed and accuracy, a balance generally referred to as the speed-accuracy tradeoff (SAT). In this study, we investigated the role of controlled SAT in a two-choice task in which manual responses were either validly or invalidly cued. Examining electrophysiological measurements of oscillatory brain activity, theta power in the anterior cingulate cortex (ACC), alpha power in the occipital cortex, and beta power in the motor cortex were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 60 publications
3
31
0
Order By: Relevance
“…Error bars represent the standard error of the mean. ** p < .01 beta power decreases over (pre) motor sites are related to the preparation of motor responses (e.g., Pastötter, Berchtold, & Bäuml, 2012;Tzagarakis, Ince, Leuthold, & Pellizzer, 2010). Specifically, it has been shown that response preparation involves a decrease of beta activities that is typically more pronounced contralateral than ipsilateral to the responding hand, reflecting response activation or release of response inhibition (e.g., Doyle, Yarrow, & Brown, 2005;Stancák & Pfurtscheller, 1996).…”
Section: Implications From Eeg Results: Retrieval Successmentioning
confidence: 98%
“…Error bars represent the standard error of the mean. ** p < .01 beta power decreases over (pre) motor sites are related to the preparation of motor responses (e.g., Pastötter, Berchtold, & Bäuml, 2012;Tzagarakis, Ince, Leuthold, & Pellizzer, 2010). Specifically, it has been shown that response preparation involves a decrease of beta activities that is typically more pronounced contralateral than ipsilateral to the responding hand, reflecting response activation or release of response inhibition (e.g., Doyle, Yarrow, & Brown, 2005;Stancák & Pfurtscheller, 1996).…”
Section: Implications From Eeg Results: Retrieval Successmentioning
confidence: 98%
“…Movement-related beta oscillations over bilateral motor cortex exhibit a sharp decrease in spectral power at the beginning of movement (Cruikshank et al, 2012; Gwin and Ferris 2012; Kilavik et al, 2013; Pastotter et al, 2012). In the current study, we did observe this classic bilateral reduction in beta band activity, with greater reductions evidenced in the contralateral hemisphere.…”
Section: Discussionmentioning
confidence: 99%
“…In the contralateral motor area, beta band activity did not change with movement acceleration at the beginning of movement, but did increase with the task condition during the deceleration phase of the movement. Beta band activity preceding a choice-reaction time task has been shown to vary as participants focus on accelerating the limb rather than accuracy (Pastotter et al, 2012). Pastotter and colleagues did not find any changes in peak beta band power after the beginning of movement.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding this, at least one study has examined the effect of SAT on the EEG frequency spectra (Pastötter et al, 2012). Using a two-choice discrimination task, subjects were cued trial-by-trial to emphasize speed or accuracy.…”
Section: Applications Of Sat Methodologymentioning
confidence: 99%